Conservation Genetics of an Urban Desert Fish, the Arroyo Chub. Issue 2 (3rd March 2016) - Benjamin, Alyssa; May, Bernie; O'Brien, John; Finger, Amanda J.
Abstract: Urbanization, habitat degradation, fragmentation, and invasive species have led to the severe decline or extirpation of many endemic southern California freshwater fish species, including the Arroyo Chub Gila orcuttii, which has declined precipitously in recent years. Classified by the California Department of Fish and Wildlife as a species of high concern, the Arroyo Chub is native to the Los Angeles, San Gabriel, San Luis Rey, Santa Ana, and Santa Margarita rivers and Malibu and San Juan creeks. To examine Arroyo Chub population structure and genetic diversity within the species' native range, we used 10 microsatellite markers to genotype 259 individuals. We observed moderate to high genetic diversity and population differentiation both between and within drainages; Bayesian clustering supported eight distinct clusters of Arroyo Chub corresponding to eight isolated populations. Of these populations, the Big Tujunga Creek population (Los Angeles River) was the least genetically differentiated (genetic differentiation index F ST = 0.048–0.208) and also had the highest genetic diversity (observed heterozygosity Ho = 0.890). Populations in Malibu Creek, Pacoima Canyon (Los Angeles River), and the Santa Margarita River were the most genetically differentiated ( F ST = 0.163–0.400), had the lowest genetic diversity ( Ho = 0.556–0.680), and showed evidence of past bottlenecks. Arroyo Chub at these localities are at risk for continued loss of genetic diversity due to drift and small population sizes; therefore, we suggest that in the event of extirpation, translocations from the most closely related source populations should be considered. However, we recommend that management efforts focus on improving habitat quality and habitat area for Arroyo Chub in order to maximize population genetic diversity and adaptive potential over time. Received July 10, 2015; accepted November 16, 2015